Central Venous Catheter-Associated Blood Stream Infections Occurring in Canadian Intensive Care Units: A Six-Month Cohort Study. Issue 3 (1st June 2006) - Holton, Donna; Paton, Shirley; Conly, John; Embree, Joanne; Taylor, Geoffrey; Thompson, William; Canadian Nosocomial Infection Surveillance Program,
Abstract : OBJECTIVE: To determine the rate and risk factors associated with central venous catheter (CVC)-associated bloodstream infections (BSIs) in Canadian intensive care units (ICUs). DESIGN: A prospective, active six-month cohort with a nested case-control study. SETTING: Forty-one ICUs located in 19 Canadian hospitals. METHODS: Data were collected using a standardized format on all CVCs and patients when a CVC was inserted for more than 48 h. Results of microbiological studies and therapeutic interventions were recorded when a BSI occurred. RESULTS: There were 182 BSIs from 3696 CVC insertions in 2531 patients. Coagulase-negative staphylococci were responsible for 73% of the BSIs. Mean rates of CVC-associated BSIs per 1000 CVC days were 6.9, 6.8 and 5.0 in adult, neonatal and pediatric ICUs, respectively. Significant factors associated with BSI included duration of CVC insertion (OR=1.2, 95% CI 1.1 to 1.3), receiving total parenteral nutrition (OR=4.1, 95% CI 1.2 to 14.3) and having one or more CVCs (OR=3.1, 95% CI 1.5 to 6.5). In the case-control study, 80% of the variance in a backward elimination logistic regression analysis was explained by duration of CVC insertion (OR=1.2 per day), receiving chemotherapy (OR=6.1), more than one CVC insertion during the study (OR=3.5), insertion of a CVC with two or more lumens (OR=2.3), using the CVC to administer total parenteral nutrition (OR=1.6) and having a surgical wound other than a clean wound (OR=1.6). CONCLUSION: The present study identified risk factors explaining 80% of the variance associated with BSIs and is one of the largest reports on the rate of CVC-associated BSIs occurring in the ICU setting.